Pemerintah di Tengah Isu Pengelolaan Tambang Tradisional Pohuwato - Prasetia, Dimas; Isa, Rusli; Nani, Yacob Noho (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the Role of Government in the Management of Traditional Mining in Pohuwato Regency as seen from: Government as a Regulator, Government as a Dynamist and Government as a Facilitator. This research method uses a descriptive approach with qualitative data analysis. Data collection techniques used are observation, interviews, documentation. Data analysis techniques through the following stages: Data Reduction, Data Presentation and Conclusions. Based on the results of the research analyzed in the field, the Role of Government in the Management of Traditional Mining in Pohuwato Regency, seen from: Government as a Regulator, Government as a Dynamisator and Government as a Facilitator, has been carried out well, but there are still some things that need to be fixed and improved, namely the lack of understanding of the community regarding the regulations set by the government. There needs to be socialization or explanation to the community regarding the regulations. As well as increasing or providing facilities that are useful for the mining community.